2020
DOI: 10.2147/dmso.s240641
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Relationship Between the Dietary Inflammatory Index and Metabolic Syndrome in Ravansar Cohort Study</p>

Abstract: The aim of this study was to investigate the association between dietary inflammatory index (DII) and metabolic syndrome (MetS) and its components using data of Ravansar non-communicable diseases (RaNCD) cohort study. Patients and Methods: The present cross-sectional study was performed using the information of 6538 participants in the RaNCD study in Iran. A validated 125-item food frequency questionnaire (FFQ) was used to acquire DII scores. MetS was defined based on national cholesterol education program-adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 60 publications
2
25
1
Order By: Relevance
“…On the other hand, associations between DII and metabolic syndrome (MetS) components including high TG and low HDL-C concentrations, high blood pressure, glucose intolerance, central obesity, CVD and liver cancer have been reported [2,[26][27][28]. Overall, the studies mentioned and our nding consistent the hypothesis that diet an important factor in the in ammation process [13,26].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, associations between DII and metabolic syndrome (MetS) components including high TG and low HDL-C concentrations, high blood pressure, glucose intolerance, central obesity, CVD and liver cancer have been reported [2,[26][27][28]. Overall, the studies mentioned and our nding consistent the hypothesis that diet an important factor in the in ammation process [13,26].…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that healthy food is inversely related to in ammation [1,2] and also several trial and metaanalysis studies have reported the association between enough intake of vitamin C, vitamin E, antioxidants and ber with lower levels of in ammatory markers [3,4,6,7]. On the other hand, associations between DII and metabolic syndrome (MetS) components including high TG and low HDL-C concentrations, high blood pressure, glucose intolerance, central obesity, CVD and liver cancer have been reported [2,[26][27][28]. Overall, the studies mentioned and our nding consistent the hypothesis that diet an important factor in the in ammation process [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the association between DII, dietary patterns or PDI with metabolic syndromes [ 9 , 10 ] or chronic diseases such as cardiovascular diseases [ 11 , 12 ], diabetes [ 12 , 13 ] and certain types of cancers [ 14 ]. However, evidence on the association between the DII, PDI or dietary patterns and obesity prevention are limited, particularly in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…shown that healthy food is inversely related to in ammation 1,2 and also several trial and meta-analysis studies have reported the association between enough intake of vitamin C, vitamin E, antioxidants and ber with lower levels of in ammatory markers 3,4,6,7 . On the other hand, associations between DII and metabolic syndrome (MetS) components including high TG and low HDL-C concentrations, high blood pressure, glucose intolerance, central obesity, CVD and liver cancer have been reported 2,[24][25][26] . Overall, the studies mentioned and our nding consistent the hypothesis that diet an important factor in the in ammation process 13,24 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, associations between DII and metabolic syndrome (MetS) components including high TG and low HDL-C concentrations, high blood pressure, glucose intolerance, central obesity, CVD and liver cancer have been reported 2,[24][25][26] . Overall, the studies mentioned and our nding consistent the hypothesis that diet an important factor in the in ammation process 13,24 .…”
Section: Discussionmentioning
confidence: 99%